Synthesis and photophysical studies of tetrazolate‐based Eu(III) photoluminescent ternary complexes containing N‐heterocyclic phosphine oxides auxiliary co‐ligands. (17th December 2015) - Mal, Suraj; Pietraszkiewicz, Marek; Pietraszkiewicz, Oksana
Abstract: Two new ternary tetrazolate Eu(III) complexes with phosphine oxide co‐ligands Eu(PTO)3 ·(P1/P2) [PTO = 5‐(2‐pyridyl‐1‐oxide)tetrazole, P1 = diphenylphosphorylamino‐phenylphosphoryl‐benzene, P2 = diphenylphosphorylpyridine)‐bis‐isobutyricphosphoryl] were synthesized and characterized using UV, fluorescence, IR and 1 H NMR spectroscopic techniques. The analytical data prove that the complexes are mononuclear in nature and the central Eu(III) ion is coordinated by three N and three O atoms of tetrazolate, and two O atoms of the corresponding bidentate phosphine oxide ligands. The ancillary ligand increased the photoluminescence efficiency of Eu(PTO)3 ·P1 (complex 3) by twofold compared with our previously reported Eu(PTO)3 complex (complex 1). Copyright © 2015 John Wiley & Sons, Ltd.